Physical activity in Brazil: a systematic review Atividade física no Brasil: uma revisão sistemática - Samuel C. Dumith (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
The purpose of this study, based on a systematic literature review, was to describe the prevalence of physical activity (or inactivity) in the Brazilian population. The databases consulted were: LILACS, SciELO, MEDLINE, Web of Science, and the Google Scholar portal. The terms "physical activity", "physical exercise", "physical inactivity", "sedentary" "Brazil", and "Brazilian" were used in the search. Overall, 47 studies (all cross-sectional) with random samples were found, and in 26 studies physical activity was the main variable. Only two studies were published before the year 2000, as compared to 12 in 2008 alone. The studies were heavily concentrated in the South and Southeast of Brazil, and there were few studies on physical activity in children and adolescents. In all the studies, physical activity was measured subjectively, mainly with questionnaires, and the most widely studied domain was leisure time. The criteria for defining physical activity varied widely, as did prevalence. The study highlighted the need for standardization of instruments, criteria, and nomenclature in epidemiological studies on physical activity. O objetivo deste estudo foi descrever, por meio de uma revisão sistemática, a prevalência de atividade (ou inatividade) física no Brasil. As bases de dados consultadas foram: LILACS, SciELO, MEDLINE, Web of Science e o portal Google Acadêmico. Os termos de busca foram: "atividade física", "exercício físico", "inatividade física", "sedentarismo", "Brasil" e "brasileiros". Foram localizados 47 estudos (todos transversais) com dados sobre prevalência de atividade física em amostras aleatórias, sendo que em 26, esta foi a principal variável. Apenas dois estudos foram publicados antes de 2000, e 12 em 2008. Houve uma grande concentração de trabalhos nas regiões Sul e Sudeste, e poucos estudos com crianças. Em todos os trabalhos, a atividade física foi mensurada de forma subjetiva, principalmente por meio de questionários, e o domínio mais estudado foi o lazer. Os critérios para definir atividade física variaram amplamente, assim como a sua prevalência. Evidencia-se a necessidade de padronização dos instrumentos, critérios e nomenclatura nos estudos epidemiológicos sobre atividade física.